(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the efficacy and safety of electroacupuncture combined with Traditional Health Preservation exercises and Juan bi pellet in the treatment of Cervical Scapulohumeral Syndrome. Subjects and Methods: A clinical interventional study was conducted on 40 patients diagnosed with Cervical Scapulohumeral Syndrome secondary to cervical spondylosis or intervertebral disc herniation at the National Hospital of Traditional Medicine. Patients received electroacupuncture according to the Ministry of Health protocol for 21 days (excluding Saturdays and Sundays), practiced Nguyen Van Huong’s Health Preservation exercises, and took Juan bi pellet for 21 days. Results: After 21 days of treatment, the mean VAS pain score decreased from 4.93 ± 0.86 to 0.55 ± 0.68 (p < 0.05). Cervical spine range of motion significantly improved after treatment (p < 0.05). The daily activity limitation score decreased from 21.75 ± 4.37 to 3.25 ± 1.61 (p < 0.05). No adverse clinical effects were observed during the 21-day treatment. Changes in laboratory parameters (RBC, WBC, PLT, AST, ALT, Urea, Creatinine) were not statistically significant (p > 0.05).